Hematological and Histomorphological Amelioration by Withania Somnifera of Cisplatin-induced Splenotoxicity in Rats - Nadia Younus; Aaqiba Rasheed; Syed Mohsin Turab; Asma Basharat Ali; Sahrish Mukhtar; Nausheen Adnan (KARACHI MEDICAL AND DENTAL COLLEGE, 2024)
Objective: This study was designed to analyse the toxic effects of the anti-cancer drug cisplatin on rat spleen and blood parameters and its amelioration by the root extract of a naturally occurring antioxidant Withania Somnifera. Methods: This experimental study was conducted in Baqai Medical University and Jinnah Medical and Dental College, Anatomy department, after the approval of Institutional Animal Ethical Committee. 60 male Albino Wistar rats, 14-16 weeks old and weighing 200-250gm were randomly divided in to 4 groups.  Group A received no treatment, group B was given intraperitoneal injection of Cisplatin only for, group C received a combination of IP cisplatin and W. somnifera root extract orally and group D was given W. somnifera root extract only. Initial and final body and splenic weights, blood and histological analysis was carried out and difference between the groups were recorded.  Statistical analysis of data was done using SPSS version 25.0. Results: The rats of Cisplatin only group B showed significant toxic changes in splenic histology: thickened splenic capsule, white pulp reduction with reduced PALS areas, central artery vacuolization. These changes were improved in cisplatin and W. somnifera group C. Blood profiles showed decreased Hb, TLC and platelets in cisplatin only group B but it was improved in the cisplatin and W. somnifera group C. Conclusion: Our study concluded that the W. Somnifera root extract protects against cisplatin induced damage to splenic tissue and hematological alterations in rat model. This ponders on its potential as an adjuvant therapy with anticancer cisplatin treatment for minimizing its side effects.